2018
DOI: 10.1016/j.otsr.2018.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Circumferential minimally invasive approach for low-grade isthmic spondylolisthesis: A clinical and radiological study of 43 patients

Abstract: One stage circumferential fixation for adults' LGIS without decompression, allows restoration of intervertebral height permitting good reduction of the slippage, an increasing of the IFS and liberation of nerve roots.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 18 publications
3
4
0
Order By: Relevance
“…Regarding clinical outcome, the scores collected were satisfactory with a mean VAS-L and VAS-R at last follow-up respectively at 2.3 and 1. These results are comparable with the series of Farah et al which included 43 patients treated with minimallyinvasive surgery, that found respectively 2 and 1 for VAS-L and VAS-R (13). Mean ODI at followup in this study was 13.8% whereas Koné et al, in a similar cohort of 27 patients, found a mean ODI at 28.7% (14).…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Regarding clinical outcome, the scores collected were satisfactory with a mean VAS-L and VAS-R at last follow-up respectively at 2.3 and 1. These results are comparable with the series of Farah et al which included 43 patients treated with minimallyinvasive surgery, that found respectively 2 and 1 for VAS-L and VAS-R (13). Mean ODI at followup in this study was 13.8% whereas Koné et al, in a similar cohort of 27 patients, found a mean ODI at 28.7% (14).…”
Section: Discussionsupporting
confidence: 88%
“…Tye et al exhibited better clinical and radiological outcomes for double approaches comparing to TLIF (12). Farah et al showed good outcomes with ALIF and percutaneous pedicle fixation (13).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The procedure can be used to treat diverse pathologies and has many benefits. Demonstrated radiographic advantages include effective restoration of disk height, reduction of spondylolisthesis, and improved spinopelvic parameters [ 2 , 3 ]. The approach allows for a complete discectomy and placement of a large interbody cage, resulting in solid anterior column support and fusion rates in excess of 90% [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…The approach allows for a complete discectomy and placement of a large interbody cage, resulting in solid anterior column support and fusion rates in excess of 90% [ 4 ]. The ALIF has also been associated with improved patient-reported outcome measures [ 2 , 5 ].…”
Section: Introductionmentioning
confidence: 99%